Almost Drowning: Data as a Troubling Anchor in an Arts/Social Science Collaboration. Issue 1 (February 2014) - Durham-DeCesaro, Genevieve; Sharp, Elizabeth
This article highlights fissures between the disciplines of dance and social sciences in approaching and valuing data and offers creative solutions for dancers and choreographers working collaboratively with scholars and artists in other disciplines. We locate our challenges in our divergent relationships with social science data, using the divergence as a framework for exploring discipline-specific practices as unintended roadblocks in collaborative, transdisciplinary research. We propose that the structure of our collaboration, particularly our unique pairing of dance and social science, and our emergent discoveries have implications beyond our home disciplines and promise to advance the growing enterprise of transdisciplinary collaboration.